The Occurrence of Aflatoxins in Date Palm (Phoenix dactylifera L.) Worldwide - Merfat Abdulrahman Almaghrabi (Journal of Food Quality)
Due to global warming, the risk of aflatoxins exposure through the consumption of contaminated food has increased. Aflatoxins pose serious health hazards to humans’ and animals’ health because of their carcinogenic, mutagenic, and teratogenic properties and their immunosuppressive effects. Aflatoxin contamination in various agricultural commodities has attracted much attention worldwide. Date palm fruits are among these important commodities that are vulnerable to fungal contamination and consequent aflatoxins production. Furthermore, dates are often consumed directly without any further processing, which may result in direct exposure to aflatoxins. Moreover, dates are the second dried fruits traded worldwide, which reflects the widespread consumption of dates due to their nutritive values in addition to religious and cultural values. Accordingly, this review summarizes and discusses the frequency and incidence of aflatoxin contamination in dates worldwide and outlines the analytical procedure for aflatoxin determination in dates for the first time. The susceptibility of date palm fruits to aflatoxins contamination has been documented at various levels in several regions. The findings urged the importance of conducting more comprehensive studies on aflatoxin occurrence and contamination levels in dates as a likely contributor to the dietary exposure to aflatoxins.